Carbon sequestration potential of agroforestry systems opportunities and challenges - Kumar, B. Mohan; Nair, P. K. Ramachandran (Springer ebooks., 2011)
This multi-authored volume contains peer-reviewed chapters from the world's leading researchers and professionals in this topic.  It is a compendium of original research articles, case studies, and regional overviews and summarizes the current state of knowledge on carbon sequestration potential of agroforestry systems.  The main hypothesis of the book is that the farmers since time immemorial have integrated an array of tree and crop species in their land use systems as a means to achieve higher productivity, risk avoidance, product diversification, and sustainability.  These multispecies production systems also impact the ecosystem processes favorably.  Yet, our understanding of the diversity attributes and carbon dynamics under agroforestry is not adequate.  Although carbon sequestration is a focal theme of discussion in most agroforestry and climate conferences, publications on carbon sequestration in agroforestry are scattered.  This book, with 16 chapters organized into three broad sections titled: Measurement and Estimation, Agrobiodiversity and Tree Management, and Policy and Socioeconomic Aspects, represent a cross section of the opportunities and challenges in current research and emerging issues in harnessing carbon sequestration potential of agroforestry systems. The book is unique in its exclusive and global coverage of the subject, and constitutes a valuable reference material for students and researchers in the field of agroforestry and climate change mitigation